Development and use of indirect liquid-phase ELISA test system for detection of PRRS virus antigen during in-process control of raw materials intended for vaccine production - Ye. P. Baborenko; O. P. Byadovskaya; D. A. Biryuchenkov; A. V. Konstantinov; R. V. Yashin (Ветеринария сегодня)
Porcine reproductive and respiratory syndrome (PRRS) being endemic and reported in the most countries in the world remains one of the most challenging diseases in pig industry. The main disease control measures include preventive vaccination and animal movement control within and outside the country as well as diagnostic testing of pigs in the population. Live and inactivated vaccines are used for specific prevention of porcine reproductive and respiratory syndrome. Complete and irreversible infectious agent inactivation with maximum epitope preservation and protective immunity in immunized animals are the main requirements for inactivated vaccines. Therefore, continuous improvement of methods for vaccine quality control at various vaccine production stages is of current importance. Results of development of the test system based on indirect liquid-phase enzyme-linked immunosorbent assay (ELISA) for PRRS virus antigen detection and activity testing in infectious and inactivated virus-containing cell cultures at intermediate stages of the vaccine production process are described in the paper. The test-system development process included purified and concentrated virus antigen as well as hyperimmune rabbit sera preparation. Specificity of purified and concentrated virus antigen was confirmed with real-time polymerase chain reaction. The developed test-system was shown to detect the virus antigen at initial infectivity titre of 4.87–7.21 lg TCID50/cm3 corresponding to ELISA titre (dilution) of 1:4 up to 1:64. Methodical Guidelines for detection of porcine reproductive and respiratory syndrome virus antigen with indirect liquid-phase enzyme-linked immunosorbent assay (ELISA) (2019) were developed based on the work results, commissioned and approved by the FGBI “ARRIAH” Scientific Board.